The Development of a National Sport Event Management Model that Affects the Value Added of the Sport Industry in Thailand - Patantiya Singcram; Thanarit Thanaiudompat (Emerging Science Journal, 2023)
The objective of this study was to construct a model of the link between sports resources and the model of national sports event management and the added value of Thailand's sports sector. Mixed methods were implemented in this study. The causative and result link between sports resource variables and national sporting practices and the added value of the Thai sports sector were examined using quantitative research. Using questionnaires and qualitative phenomenological research, data were obtained from 207 sports competition management organizations registered with the Department of Business Development in 2020. Based on in-depth interviews, a group discussion with the Council of Industry Committees was implemented to corroborate the results of the in-depth interviews. The sports industry group comprised of three individuals and two academics in sports business management who conducted a corroborative elemental analysis on the data. And structural equation models. The hypothesis research found that 1) sports resources had a direct effect on the value added of the sports industry and an indirect effect on the value added of the sports industry through the national sports competition management; 2) the sports resources had a direct effect on the national sports competition management; and 3) the national sports competition management had a direct effect on the added value of the sports industry in Thailand. The analysis revealed that the hypothetical model was consistent with the statistical data. It appeared to be qualified with χ2 = 47.85, p-value = 0.08, χ2/df = 1.55, GFI = 0.96, AGFI = 0.98, and RMSEA = 0.01. The contribution of this research is that it can explain the relationship between the causes and outcomes of sports resources and guidelines for organizing national sports events and the added value of the sports industry in Thailand. The results of the study can be used in the management of sports competition management businesses, which leads to sustainable performance for the sports industry. Doi: 10.28991/ESJ-2023-07-02-010 Full Text: PDF